A Sociological Approach: the portrait of society in Thomas Hardy’s The Mayor Of Casterbridge - Masri Masri (English Teaching and Linguistics Journal (ETLiJ), 2021)
This writing analyzed ‘The Mayor of Casterbridge’ by Thomas Hardy, a great novelist of Victorian age through a sociological approach. The Sociological Approaches has two purposes that a literary work can be regarded as the portrayal of aspect of life and regards literature in its milieu. Literary works bring us back to the reality of human situation such as conflicts, feeling, and relationships between individuals and the society in which they live, present characters who are at odds with the society. In analysing the study, the approach was combined with the Mimetic theory. The sociology of literature is applied in this research for it brings the understanding of  literature in relation to the society. It explains that literary works could be as an imitation which reflects the reality. Although literary works are imaginatively consumed, but the imaginative framework cannot be understood outside the empirical framework and literary work is not merely an individual symptom but a social phenomenon. The objective of this study is to find out and describe that the novel portrays the condition of society, the life, the people and the changes happened through the element of sociology of literature. This writing discussed the relation of literature and sociology from the characters, the setting and events in the novel, how it portrayed the poverty and hard life, conditioning of the poor and the rich, and the change of the social system.